REDESIGN USER INTERFACE DAN USER EXPERIENCE APLIKASI KRL ACCESS BERBASIS MOBILE DENGAN METODE DESIGN THINKING DAN PENDEKATAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Amelia Azzahra Chairun Nisa (2023)
PT. KAI Commuter Jabodetabek, as a provider of public transportation services in the Jabodetabek area and its surroundings, has implemented an information technology solution called the KRL Access Mobile Application. However, only 0.406% of the total KRL Jabodetabek users in 2022 utilized the KRL Access Mobile Application, despite PT. KAI Commuter Jabodetabek suggesting its use as a means to access information and train schedules. In order to ensure user satisfaction and understand the User Experience (UX) of the application, researchers conducted a survey using the User Experience Questionnaire (UEQ) approach with 100 respondents. The survey evaluated the application across six scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The evaluation results of the KRL Access Mobile Application using the UEQ benchmark revealed that the perspicuity scale was rated below average, while the other five scales-attractiveness, efficiency, dependability, stimulation, and novelty-were rated as bad. Furthermore, during the survey, researchers collected criticisms and suggestions from respondents, which were organized into an Affinity Diagram and resulted in 73 Insight Cards. Based on this evaluation, 17 UI/UX design-related issues were identified and categorized into the six UEQ scales. This study produced 30 redesign solutions for the application, presented in the form of a high-fidelity prototype using Figma as a design development tool. The Design Thinking method was employed in the development of the application design. The research findings indicated an improvement in the User Experience quality of the KRL Access Mobile Application after the redesign, measured across the six UEQ scales, with an overall average score of 1,471. It is expected that the proposed solutions can be implemented in the KRL Access Mobile Application to support the realization of PT. KAI Commuter Jabodetabek's Vision and Mission.